Modelling EU bioeconomy credentials in the economic development framework: the role of intellectual capital - Cristea, Mirela; Noja, Graţiela Georgiana; Marcu, Nicu; Siminică, Marian; Ţîrcă, Diana-Mihaela (Technological and Economic Development of Economy, 2020)
Given the global importance of bioeconomy for sustainable development and its trendiness in the knowledge driven literature, our research aims to develop a general assessment framework for several shaping factors of bioeconomy fundamentals within the European Union under the decisive impact of the intellectual capital credentials, namely educational attainment, research and development activities and innovation patterns. Considering that there is a high heterogeneity among Member States (MS), selectively regarding the implementation of the intellectual capital in the knowledge economy, but also a differential degree of bioeconomy advances, we have compiled distinct panels on the two groups of EU-28 MS, namely EU-15 (old MS) and EU-13 (new MS). The purpose is to examine the inferences of the intellectual capital in the context of economic development and to shape its role in achieving a sustainable bioeconomy. We have applied several macro-econometric procedures for each considered group, namely: multifactorial macro-econometric models, structural equation modelling (SEM) and Gaussian Graphical Models (GGM), for the period 1995-2016. The results highlight that education, innovation and research, along with main bioeconomy credentials, are at the core of economic development of both EU-13 and EU-15 countries, having distinctive dissimilarities between them, particularly enhanced for the new EU-13 MS.First published online 25 August 2020